Morphological, Physiological and biochemical responses to soil water deficit in seedlings of three populations of wild pear tree (Pyrus boisseriana) - Zarafshar, Mehrdad (2014)
Fil: Zarafshar, Mehrdad. Tarbiat Modares University. Faculty of Natural Resources and Marine Sciences. Department of Forestry. Imam Reza St. Nour. Mazandaran Province, Iran.